2011
DOI: 10.25077/jpi.13.2.83-91.2011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of the Three Pig Keeping Systems on Performance of Small-Scale Pig Farmers at Manokwari, West Papua

Abstract: Pig keeping systems consisted of extensive, semi-intensive and intensive systems were studied to seek its performances on pigs and small-scale pig farmers. From six districts and 15 villages, 50 respondents were chosen. Characteristic of farmers and pig keeping systems were studied. Animal number used were 355 tails for measuring pig variables consisted of body weight, reproduction and herd size. Labor and experience were varied among the three pig keeping systems (P<0.05). Animal herd, farrowing rate, sucklin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Both sources of feed are obtained from restaurant waste, vegetable waste, banana peels, cassava, tofu dregs, fish market waste and kitchen. The results of this study are in accordance with the results obtained by Awom (2010), Yafur (2008) and Iyai (2008) in their studies. In this system of rearing, the pigs scavenge to feed in the morning in gardens or in areas where it is possible to get food, then in the afternoon, the pigs return to the owner's pens.…”
Section: Feed For Pigssupporting
confidence: 93%
See 2 more Smart Citations
“…Both sources of feed are obtained from restaurant waste, vegetable waste, banana peels, cassava, tofu dregs, fish market waste and kitchen. The results of this study are in accordance with the results obtained by Awom (2010), Yafur (2008) and Iyai (2008) in their studies. In this system of rearing, the pigs scavenge to feed in the morning in gardens or in areas where it is possible to get food, then in the afternoon, the pigs return to the owner's pens.…”
Section: Feed For Pigssupporting
confidence: 93%
“…In addition, there are also farmers who provide feed in the morning before the pigs scavenge for food far from the vicinity of the farmers. This is in accordance with the research of Iyai (2008) and Warastuti (2001) who reported that the feed obtained for pigs is mainly from gardens. Some breeders provide protein source feed that comes from industrial waste (tofu dregs) because they are easily obtained in the villages where the farmers keep the pigs.…”
Section: Feed For Pigssupporting
confidence: 93%
See 1 more Smart Citation
“…2008) or West Papua (Iyai and Randa 2011) as well as smallholder systems in East Africa (Chiduwa et al 2008). As becomes clear from comparing average and maximal numbers in Table 2, differences between farmers were pronounced although average animal numbers at any given time were still low.…”
Section: Discussionmentioning
confidence: 95%